Binding to thrive : Decoding Atopobium spp. interactions with host proteins and immune cells - Frick, Inga Maria; Neumann, Ariane ; 0000-0002-8636-730X (Anaerobe, 2025)
Objectives: Gram-positive anaerobic cocci are opportunistic pathogens that exploit immune suppression or tissue injury to establish infections. Atopobium spp. are clinically relevant, being linked to bacterial vaginosis, abdominal wounds, pelvic abscesses, and dental infections. While clinical reports describe the involvement in detrimental host conditions, in-depth knowledge is missing to understand how these bacteria acquire essential nutrients to evade immune responses and directly interact with the human host. Methods: Here we analyzed the growth of three blood-isolated Atopobium strains in different media and compared them to Finegoldia magna. Using radioactive binding studies, human serum albumin (HSA), a major component of serum, was identified as the primary binding partner, subsequently facilitating bacterial growth by providing essential nutrients. Next, we investigated the ability of Atopobium to interact with human blood-isolated neutrophils. Results: Interestingly, Atopobium triggered neutrophil activation, detected by increased reactive oxygen species (ROS) production, secretion of the sepsis marker heparin-binding protein (HBP), and the induction of extracellular trap (NET) formation. Conclusions: These findings provide new insights into how Atopobium utilizes host serum components and facilitates host interactions, highlighting their potential role in immune modulation and pathogenesis.
Keywords: Atopobium; Bacterial vaginosis; Fannyhessea; Gram-positive anaerobic cocci; Host-pathogen interactions